Genome-Wide Investigation of the PtrCHLP Family Reveals That PtrCHLP3 Actively Mediates Poplar Growth and Development by Regulating Photosynthesis - He, Fang; Shi, Yu-Jie; Chen, Qi; Li, Jun-Lin; Niu, Meng-Xue; Feng, Cong-Hua; Lu, Meng-Meng; Tian, Fei-Fei; Zhang, Fan; Lin, Tian-Tian; Chen, Liang-Hua; Liu, Qin-lin; et al. (Frontiers in Plant Science, 2022)
Chlorophyll (Chl) plays a crucial role in plant photosynthesis. The geranylgeraniol reductase gene (CHLP) participates in the terminal hydrogenation of chlorophyll biosynthesis. Although there are many studies related to the genome-wide analysis of Populus trichocarpa, little research has been conducted on CHLP family genes, especially those concerning growth and photosynthesis. In this study, three CHLP genes were identified in Populus. The evolutionary tree indicated that the CHLP family genes were divided into six groups. Moreover, one pair of genes was derived from segmental duplications in Populus. Many elements related to growth were detected by cis-acting element analysis of the promoters of diverse PtrCHLPs. Furthermore, PtrCHLPs exhibit different tissue expression patterns. In addition, PtrCHLP3 is preferentially expressed in the leaves and plays an important role in regulating chlorophyll biosynthesis. Silencing of PtrCHLP3 in poplar resulted in a decrease in chlorophyll synthesis in plants, thus blocking electron transport during photosynthesis. Furthermore, inhibition of PtrCHLP3 expression in poplar can inhibit plant growth through the downregulation of photosynthesis. Ultimately, PtrCHLP3 formed a co-expression network with photosynthesis and chlorophyll biosynthesis-related genes, which synergistically affected the growth and photosynthesis of poplars. Thus, this study provides genetic resources for the improved breeding of fast-growing tree traits.